2016
DOI: 10.1016/j.jacc.2016.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a Driver of Adverse Left Ventricular Remodeling After Acute Myocardial Infarction

Abstract: Treatment of acute myocardial infarction (AMI) has improved significantly in recent years, but many patients have adverse left ventricular (LV) remodeling, a maladaptive change associated with progressive heart failure. Although this change is usually associated with large infarcts, some patients with relatively small infarcts have adverse remodeling, whereas other patients with larger infarcts (who survive the first several days after AMI) do not. This paper reviews the relevant data supporting the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
345
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(360 citation statements)
references
References 75 publications
5
345
0
10
Order By: Relevance
“…The mechanism of harmful heart remodelling after a MI includes numerous cellular, extracellular and neurohumoral components 8 and in most cases, the size of scar formed is proportionate to the severity of heart remodelling, but it has also been demonstrated that size of scar need not translate into severe heart remodelling. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of harmful heart remodelling after a MI includes numerous cellular, extracellular and neurohumoral components 8 and in most cases, the size of scar formed is proportionate to the severity of heart remodelling, but it has also been demonstrated that size of scar need not translate into severe heart remodelling. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is at the center stage of pathologic cardiac remodeling and heart failure. 29,30 Previous reports have shown that lessened T-cell activation is correlated with diminished cardiac inflammation in the setting of POL. 5,6 We presented that TMRKO mice manifested reduced cardiac inflammation in parallel with improved cardiac remodeling, as well as decreased T-cell accumulation and activation in the heart after POL.…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 We next determined whether TMRKO affected cardiac inflammation. Accumulation of myeloid cells in the heart was first analyzed using flow cytometry ( Figure S5).…”
Section: T-cell Mr Deficiency Decreases Aac-induced Cardiac Inflammatmentioning
confidence: 99%
“…

A long‐term, inappropriate, and excessive inflammatory process contributes importantly to the progressive myocardial deterioration that occurs after AMI and that occurs in patients with HF.

The concept that the progressive deterioration of cardiac function seen in both AMI and HF is in part caused by an excessive persistent inflammatory response has a compelling experimental basis supporting its validity 11, 12. For example, in the setting of AMI, there is a subgroup of patients whose progressive deterioration in left ventricular function is not caused solely by the AMI‐induced magnitude of myocardial damage, but involves other mechanisms 13. Chronic inflammation has been postulated as being one of these mechanisms responsible for progressive myocardial dysfunction in AMI, and also in HF 11, 12, 13, 14, 15

…”
mentioning
confidence: 99%
“…For example, in the setting of AMI, there is a subgroup of patients whose progressive deterioration in left ventricular function is not caused solely by the AMI‐induced magnitude of myocardial damage, but involves other mechanisms 13. Chronic inflammation has been postulated as being one of these mechanisms responsible for progressive myocardial dysfunction in AMI, and also in HF 11, 12, 13, 14, 15

Systemic anti‐inflammatory effects of MSCs constitute one of the major mechanisms by which MSCs may improve left ventricular function.

Any myocardial benefit provided by stem cell administration is undoubtedly not caused by repopulating the damaged myocardium with new myocytes, but rather by paracrine activities with a diverse array of beneficial effects 12, 16, 17.

…”
mentioning
confidence: 99%